2002
DOI: 10.1515/jpm.2002.061
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium concentration in maternal and cord blood and infant birth weight: a study on healthy non-smoking women

Abstract: The aim of our study was to measure, at delivery, maternal and cord blood cadmium levels (by means of atomic absorption spectrometry) in 45 healthy non-smoking pregnant women exposed to a low cadmium challenge, and to evaluate the relationship between these cadmium levels and the birth weight of the infants. Our results showed fairly low cadmium levels in maternal blood, in accordance with the fact that all women enrolled in this study lived in areas with low toxic metal contamination and that they did not smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 22 publications
3
54
0
Order By: Relevance
“…It also decreases production of hCG and inhibits placental transfer of oxygen and nutrients to the fetus [17]. Preterm delivery and lower birth weight of newborn infants were reported in women occupationally exposed to Cd and also the birth weight is inversely correlated with maternal and cord blood Cd concentrations [18]. Laudanski et al [19] reported that the mean blood concentration of Cd in mothers of preterm infants was higher than that of women who went to full term in an area with high amounts of lead and cadmium in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…It also decreases production of hCG and inhibits placental transfer of oxygen and nutrients to the fetus [17]. Preterm delivery and lower birth weight of newborn infants were reported in women occupationally exposed to Cd and also the birth weight is inversely correlated with maternal and cord blood Cd concentrations [18]. Laudanski et al [19] reported that the mean blood concentration of Cd in mothers of preterm infants was higher than that of women who went to full term in an area with high amounts of lead and cadmium in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…This metal is highly toxic at low concentrations. It is known to accumulate in the placenta and even low levels might be a risk factor for lower birth weight, reflecting developmental impairment in infants (Salpietro et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of cadmium's bioavailability, accumulation in the environment, and long biological half-life is only one factor that contributes to maternal exposure and increased risk of FGR. Additionally, clinical studies have reported significantly higher levels of cadmium in the placentas of growth-restricted babies born to smoking mothers (14,25,31,40,45,65). Moreover, animal studies have shown that maternal cadmium exposure leads to FGR (1, 2, 6, 8, 15, …”
Section: Discussionmentioning
confidence: 99%
“…MT-I AND -II PROTECT AGAINST CADMIUM-INDUCED FGR 16,20,32,40,45,47,58). However, the molecular mechanisms underlying cadmium-induced FGR remain largely unknown.…”
Section: E731mentioning
confidence: 99%